Number 21 (February 1990) - Southern Fishes Council (Southeastern Fishes Council Proceedings, 1990)
(February 1990) - Aspects of the Life History of the Blue Shiner, Notropis caeruleus, in the Consauga River, Georgia. By R.S. Krotzer, 2 pp. Decline of the Alabama Shad, Alosa alabamae in the Pearl River, Louisiana-Mississippi: 1963-1988. By G.E. Gunning and R.D. Suttkus, 2 pp. Mating Behaviors of the Blacktail Shiner, Cyprinella venusta, from Southeastern Mississippi. By D.C. Heins, 3 pp., plus News Notes.
Keywords: fishes; blue shiner; notropis caeruleus; consauga river; alabama shad; alosa alabamae; pearl river; blacktail shiner; cyprinella venusta